Os componentes naturais e a fragilidade ambiental dos sertões do semiárido sergipano - Freitas, Éder Guedes (2024)
The discussion of environmental issues in the semi-arid region has become very relevant, thanks to the fragility and vulnerability of these environments. The semi-arid region of Sergipe is marked by the degradation of its primary forest cover. This calls into question the very capacity for land use and can make these areas susceptible to environmental degradation and desertification. This situation can be seen in the nine municipalities that make up Sergipe's Sertão do São Francisco micro-region, which have had their territorial dynamics shaped by the different economic activities developed. From this perspective, it is essential to implement public policies that focus on sustainable territorial planning. Anchored in this need, the aim was to discuss the environmental planning process by identifying indicators of environmental fragility and vulnerability in order to support geo-environmental zoning. In order to achieve its objectives, this work was based on a systemic approach, allowing for the recognition and delimitation of the environmental systems that make up the landscape. Five environmental systems were delimited: Plains and River Terraces, Pre-Littoral Tablelands, Sedimentary Plateaus, Hinterlands and Residual Surfaces, each resulting from different evolutionary processes, with the hinterlands being the largest, covering an area of 5,093.01 km². Once the environmental units had been recognized, the environmental fragility and vulnerability indicators of the research area were analyzed, showing that most of the territory has high degrees of fragility, ranging from medium to very high fragility areas, with very high fragility areas restricted to small portions of the territory. The degrees of vulnerability ranged from moderate to high throughout the region, especially in the municipalities of Canindé de São Francisco, Monte Alegre de Sergipe and Poço Redondo, affecting the marginal areas of rivers, springs and urban areas, which presented conditions of vulnerability ranging from high to very high, resulting from the form of urbanization used, and the intensive exploitation of natural resources and the advance of productive areas, which results in the reduction of vegetation cover and intensification of erosion processes. Based on the recognition of the degrees of fragility and vulnerability of each environmental unit, it was possible to draw up the geo- environmental zoning chart, defining 25 zones, which specify the degree of associated risk, fragility and vulnerabilities of each unit, with the prevalence of units with a tendency to instability or unstable, with greater susceptibility to degradation and, consequently, desertification. Finally, we can see that the methodology developed in this work showed results that were very consistent with local characteristics and was less generalist than the other methodologies presented, thus showing great potential for assessing degrees of fragility and using them as a planning and land-use planning tool.